2020
DOI: 10.25122/jml-2020-0173
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change and Social Campaigns

Abstract: The impact of climate change on humanity and nature is increasingly evident. The atmosphere and oceans have warmed, leading to rising sea levels, a sharp drop in Arctic sea ice, floods, heatwaves, and fires. Calls to action are getting stronger. Concerns about climate change have become a full social movement, stimulating climate activism from the bottom up to the world, especially among young people. Campaigns are initiated by governments and international organizations, scientists and scientific institutions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…In 2016 in Paris, countries agreed to minimise the rise in global average temperature and achieve net zero carbon emissions by 2050 (UNFCCC, 2015) (A6) and in 2021 at COP26 in Glasgow, 45 world leaders committed to accelerate innovation and deployment of clean technologies this decade, with annual progress assessed in Breakthrough Agenda Reports (IEA, 2022). A noticeable increase in climate activism and rethinking of food systems, including moves to more plant-based diets (Poppy & Baverstock, 2019;Bhunnoo & Poppy, 2020;Raducu et al, 2020), plus international poll results, have indicated strong, global, public support for action to tackle climate change (Flynn et al, 2021;Gaffney et al, 2021) (A1, A3, A14, B6, C5).…”
Section: A Societymentioning
confidence: 99%
“…In 2016 in Paris, countries agreed to minimise the rise in global average temperature and achieve net zero carbon emissions by 2050 (UNFCCC, 2015) (A6) and in 2021 at COP26 in Glasgow, 45 world leaders committed to accelerate innovation and deployment of clean technologies this decade, with annual progress assessed in Breakthrough Agenda Reports (IEA, 2022). A noticeable increase in climate activism and rethinking of food systems, including moves to more plant-based diets (Poppy & Baverstock, 2019;Bhunnoo & Poppy, 2020;Raducu et al, 2020), plus international poll results, have indicated strong, global, public support for action to tackle climate change (Flynn et al, 2021;Gaffney et al, 2021) (A1, A3, A14, B6, C5).…”
Section: A Societymentioning
confidence: 99%
“…Typically, these campaigns strive to educate, create awareness, and influence the public perception regarding the science, challenges, and policies related to climate change (Segerberg, 2017;Raducu et al, 2020). Numerous studies indicate that the efficacy of such campaigns lies in their potential to alter public attitudes and behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Viewed as such, the awareness toward the negative effects of climate change is very much needed. Until now, efforts to raise people awareness on climate change has been carried out through public campaigns initiated by governments, international organizations, scientists, civil society, public and political intellectuals, religious leaders, cultural observers, and entertainers (Raducu, et al (2020;456). Over time, the rapid development of communication technology has influenced the key stakeholders in climate change issues to involve celebrities or public figures in raising awareness on climate change through creative campaigns.…”
Section: Introductionmentioning
confidence: 99%